Molecular identification of Ascaridia columbae in the Local Healthy Pigeon (Columba livia domestica, Gmelin, 1780) in Karbala Province - 1 Dhiaa J.Hamzah, 2Ihsan k. A. Al kardhi, 3 Haider A. H. Al saegh, 4 Hayder A. Muhammed , 4 Firas AL (Indian Journal of Forensic Medicine & Toxicology, 2020)
The current study was conducted to investigate dissemination of gastrointestinal Ascariasis in local pigeons (Columba livia domestica) living in Kerbala province. Forty domestic pigeons with different ages were purchased from different markets. Each bird was examined for intestinal parasites. Out of 40 birds examined, the prevalence of gastrointestinal Ascariasis in examined birds were ( 12.5% ), Ascaris sp. was detected in 100% of intestinal contents using macroscopic and microscopic examination assays, molecular diagnosis from bird belly, with the emphasis on primer designed specificity it used in our study.